Riesgo cardiometabólico del sedentarismo - Arocha R, J. Ildefonzo (Revista Hospital Clínico Universidad de Chile, 2021)
Sedentary behavior is spreading among society, especially since the rise of technology and progress. The sedentary lifestyle habits are being transmitted to young people, who increase the time they spend in sedentary activities like video games or TV. It has been demonstrated that both sedentary behavior and physical inactivity have negative cardiometabolic consequences for the health, and they become a serious problem for public health, as it has been claimed in several studies and by scientific statements. This review intent to make a call of attention to this problem that will have profound impact in the near future in many countries in Latin America.